ASSOCIATION OF ANAEMIA WITH DIETARY PRACTICES IN ADOLESCENT GIRLS - mahmood, Rabia; Khan, Rukhsana; Saleem, Shemaila (Pakistan Journal of Physiology, 2018)
Background: Anaemia is one of the ten most serious public health problems world over. Adolescent girls are more at risk to be anaemic due to their rapid growth, hormonal changes, imbalance between food intake and requirement and onset of menarche. This may lead to impaired intellectual growth, development, immunity and reproductive abilities. This study was planned to assess the prevalence of anaemia and its association with dietary habits in adolescent girls of District Rawalpindi. Methods: This cross-sectional analytical study was conducted in six villages of two union councils of district Rawalpindi. A sample of 104 randomly selected unmarried adolescent girls (11–19 years) was included in the study. Portable haemoglobin meter (Hemocue) was used to estimate haemoglobin levels. Demographic data was obtained by a self-structured questionnaire. Dietary variables were collected by using food frequency questionnaire and 24 hour’s dietary recall method. Analysis was done using SPSS-21 and Nutrisurvey software. Results: The study revealed that 71.2% of adolescent girls were anaemic. The prevalence of mild, moderate and severe anaemia amongst the girls was found to be 53.8%, 15.4% and 1.9% respectively. The results revealed that girls who had anaemia were also found deficient in vitamin A and zinc. Conclusion: Anaemia in girls of rural area in district Rawalpindi was found to be substantially high in younger adolescents (9–14 years). Anaemia was significantly associated with vitamin A and zinc deficiency. Nutritional awareness and counselling for adolescent girls in community and educational institution is recommended.